CFD ANALYSIS OF COOLING WATER FOR LIGHT-TRANSMITTING BLOCK OF A SOLAR THERMOCHEMICAL REACTOR - Ahmadov, Khushdil (Innovatsion texnologiyalar, 2024)
Due to the high temperature of solar thermochemical reactors that produce hydrogen, the glass that receives the concentrated light flux is deformed. Therefore, it is necessary to cool the bottle, which leads to the modernization of the reactor design. The light-transmitting unit of the solar thermochemical reactor has a metal body and a lighttransmitting glass. The metal body is made in the form of a hollow cylinder with two holes on the side for water circulation. On both sides of the housing there are light-transmitting windows with sealed gaskets, secured by covers equipped with holes for bolted connections to the housing. Based on the results of the research, the cooling water cycle for the block was optimized for different temperature ranges of the radiant unit of the solar thermochemical reactor. This study was simulated in COMSOL Multiphysics. With the speed of incoming water to cool the light aperture block of the solar thermochemical reactor being 1 m/s and the inlet opening being 4-4.5 mm, the amount of water coming out every second is close to 1 mole, and we can supply water to the two-stage thermochemical cycle by sending this heated water directly to reactor